Persistent Vascular Remodeling and Leakiness are Important Components of the Pathobiology of Re‐bleeding in Hemophilic Joints: Two Informative Cases. (July 2016) - Kidder, Wesley; Chang, Eric Y.; M. Moran, Colleen; Rose, Steven C.; von Drygalski, Annette
Abstract: Objective: It is unclear if vascular remodeling in hemophilic joints perpetuates bleeding because it is difficult to gauge leakiness in the setting of low clotting factor levels. Two patients provided the unique opportunity to demonstrate that vascular changes directly contribute to joint bleeding. Approach and Results: Two patients had severe hemophilic arthropathies; joint vascularity and bleeding were studied during periods of normalized plasma clotting factor activities with MSKUS and PD. One patient was "cured" of hemophilia with liver transplantation. Abnormal elbow vascularization persisted despite normalization of coagulation status and was associated with severe bleeding years after transplant. Dynamic vascular changes were detected prior to and during bleeding; angiography revealed enlarged, thickened vessels consistent with remodeling, and required arterial embolization. The second patient had continued knee bleeding and fluctuating vascular changes for months following knee replacement, unresponsive to intense daily factor treatment. Subsequently, new bleeds developed in other joints associated with similar vascular changes despite continued factor replacement. Conclusions: Vascular remodeling contributes to perpetuated hemophilic joint bleeding and therefore contributes to progressive arthropathy. Intra‐articular or systemic administration of anti‐angiogenic drugs, such as vascular endothelial growth factor antagonists, might be of benefit in such patients, but requires study.